The Influence of Market Orientation and Entrepreneurial Orientation on Competitive Advantage with Product Innovation as an Intervening Variable - Rizqiyyah, Ayu Wirani; Supriyono, Supriyono; Rusdianto, Hutomo; Kholil, Masrukhan (Global Health Science Group, 2023)
This research aims to analyze the extent of the influence of market orientation and entrepreneurial orientation in building competitive advantage with product innovation as an intervening variable at Gravitasi Teras Muria Café and Resto. The population in this study were all visitors who had come and made purchases at Gravitasi Teras Muria Café and Resto. The research results show that market orientation has no effect on competitive advantage, entrepreneurial orientation has no effect on competitive advantage, market orientation has a positive and significant effect on product innovation, entrepreneurial orientation has a positive and significant effect on product innovation, product innovation has a positive and significant effect on competitive advantage, orientation the market has a positive and significant effect on competitive advantage through product innovation as an intervening variable, and entrepreneurial orientation has a positive and significant effect on competitive advantage through product innovation as an intervening variable.